Regioselective Palmitoylation of 9-(2,3-Dihydroxy- propyl)adenine Catalyzed by a Glycopolymer-enzyme Conjugate - Jana Brabcová; Jiří Blažek; Marcela Krečmerová; Jiří Vondrášek; Jose Palomo; Marie Zarevúcka (Molecules, 2016)
The enzymatic regioselective monopalmitoylation of racemic 9-(2,3-dihydroxypropyl)- adenine (DHPA), an approved antiviral agent, has been performed by an immobilized form of Candida antarctica B lipase (CAL-B) using a 4:1 DMF/hexane mixture as the reaction medium. To improve the chemical yield of the desired monopalmitoylation reaction, solid-phase chemical modifications of the lipase were evaluated. The reaction yield was successfully increased obtaining 100% product after a second treatment of the product solution with fresh immobilised chemically glycosylated-CAL-B.